Managers' support on implementation of maternal guidelines, Limpopo province, South Africa - Ireen T. Ramavhoya; Maria S. Maputle; Dorah U. Ramathuba; Rachel T. Lebese; Lizzy M. Netshikweta (AOSIS, 2020)
Background: The report of Saving Mothers indicated a decline of maternal mortality from 12.8% to 12.5% last triennium of 2017. This shows that regardless of availability of national maternal health guidelines, midwives and managers, 25% of maternal deaths were caused by preventable and avoidable factors. As such, support provided by managers is vital in promoting the utilisation of maternal guidelines. Objectives: The objective was to determine the support offered by managers to midwives during the implementation of maternal health guidelines. Method: The study design was cross-sectional descriptive in a quantitative domain. Simple random sampling was used to select 58 operational managers and two maternal managers. Data were collected using self-administered questionnaires and analysed using Statistical Package for Social Sciences version 23. Descriptive statistics provided by Microsoft Excel in the form of charts was used to describe data. Pearson's correlation test was used to describe relationships amongst variables. Results: The results revealed that 83.3% respondents indicated a shortage of staff to attend pregnant women. Fifty-six per cent of managers indicated that shortage of material resources contributed to substandard implementation of maternal guidelines. Supervision and monitoring of implementation of maternal guidelines was difficult as indicated by 53.3%, and 63.3% indicated lack of supervision. Conclusion: Limited support in terms of monitoring and supervision by managers was strongly indicated as having a negative effect on implementation of maternal guidelines. Capacity building was offered; however, shortage of resources led to poor implementation of maternal guidelines by midwives.